La puissance des clichés langagiers dans La Cousine Bette de Balzac : entre le dévoilement de stéréotypes et leur reconnaissance par le lecteur contemporain - Kamińska, Aleksandra (Romanica Silesiana, 2021)
The aim of this article is to examine the stereotypy in Balzac’s novel Cousin Bette, by relying on the scene of a famous confrontation between Célestin Crevel and his metaphysical opposite – Baroness Hulot d’Ervy. José-Luis Diaz underlines that the Balzacian stereotype imposes itself as the imitation of the social norm and all kinds of linguistic, sartorial, behavioral automatisms etc. His research justifies the use of the concept of stereotype in relation to Balzac’s creation, especially because the nineteenth century only knows its meaning in printing. Thanks to the notion of stereotype, we can question on its influence on the behavior of the protagonists. We are also able to identify the character of the social norm of the time and its regulatory mechanisms. On the one hand, the excessively fixed language, like the cliché, allows the writer to imitate the material preoccupations of the bourgeoisie under the July Monarchy by forging, in the reader’s mind, his negative image. On the other hand, this analysis shows that the protagonist’s expression goes beyond linguistic mimicry. The stereotype allows a certain stylistic originality by which the protagonists give the reader a look into their belief systems. In this sense, the stereotype is a mechanism of regulation : it complicates the characters, creates an impression of reality. Finally, this stylistic enity capture the reader’s attention with logically permissible ideas that are morally unacceptable.